Life Survival, Social Network, and Social Capita Matrilineal of Minangkabau Women Street Vendors during Covid-19 Pandemic in West Sumatera - Irwan, Irwan; Mesra, Romi; Hamsah, Hamsah; Kuswanti, Ana; Febriani, Eka Asih; Zusmelia, Zusmelia; Siska, Felia (Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aimed to analyze life survival strategy, social networks, and social capital measured from the networks, faith, and norms of Minangkabau Woman Street Vendor during the COVID-19 pandemic in the tourism destination area of West Sumatra. This research uses a mixed method. This research had a post-positivistic paradigm with the research locations in the tourist destination areas such as Padang City, Bukittinggi City, Sawahlunto City, and Tanah Datar Regency. The results showed that women street vendors performed life survival in tourism destination areas by strengthening social capital and human capital for a better economy.Â